Quality of propolis commercialized in the informal market - Tagliacollo,Victor Alberto (2011)
The purpose of this research was to evaluate the quality of propolis produced and commercialized informally in São Paulo State through physicochemical analyses of ethanolic extracts of propolis (EEP). Thus, 40 samples of in nature propolis, provided by beekeepers from 32 towns, were analyzed. The EEP were prepared in a proportion of 30% (w/v), and the physicochemical tests were performed according to the Technical Regulation of Propolis Identity and Quality. The pH of each EEP sample was also evaluated. Regarding the dry extract, it was observed that 80% of the samples meet the minimum requirements established by the Brazilian legislation. With regard to the oxidizing property, 67.5% of EEP were below the maximum time allowed for oxidation. With regard to the solubility in lead acetate, 97.5% of the samples showed positive results, whereas no sample produced a negative result in terms of solubility in sodium hydroxide. Regarding the concentration of flavonoids, 95% of the samples produced results consistent with the minimum value allowed, and regarding the phenolic compounds, all samples were in accordance with the legislation. The EEP pH was slightly acidic. Therefore, it can be concluded that most EEP is consistently in accordance with the Brazilian legislation, which suggests that good quality propolis is produced by those beekeepers.